Behavioral marketing : delivering personalized experiences at scale - Walters, Dave, 1968- (Hoboken, NJ : Wiley, 2015)
"This book focuses on fixing marketers' highly inefficient processes and spotty results and describes how to be more "revenue predictable". The book explains the key principles of behavioral marketing, which include: customer journey mapping, channel-level planning, data capture and hygiene, campaign creation, delivery best practices, and measurement/optimization. It will include up to 10 case studies across multiple industries highlighting the revenue growth and process efficiencies resulting from great behavioral-driven marketing."--
Includes index.
Machine generated contents note: Foreword (Bill Nussey) Acknowledgments The Behavioral Marketing Manifest Chapter 1: Behavioral Marketing: More Sophisticated Audiences, Smarter Tactics and Deeper Personalization for All Chapter 2: Where Are You on The Behavioral Marketing Spectrum? Chapter 3: Gearing-Up for Behavioral Marketing: The Roles, People and Systems Needed to Win Chapter 4: Pacing Yourself: Behavioral Marketing at the Speed of Business Chapter 5: Bringing Behavioral Marketing To Life in the Real World Chapter 6: Upping Your Content Game: Educating Customers Throughout the Entire Cycle Chapter 7: Customer Journey Mapping: Putting Yourself in the Customer's Shoes Chapter 8: Channel-Level Planning: Delivering Insane Relevance Every Time Chapter 9: Data Capture and Hygiene: You're Only as Good as Your Database Chapter 10: Campaign Creation: Segments, Logic and Automation are Your Friends and Great Creative Matters More Than Ever Chapter 11: Behaviors and Mobile: Yes, It's Radically Different Than Every Other Channel Chapter 12: Measurement and Optimization: Creating a Framework and Moving Your Own Goalposts Chapter 13: It's All About the Team: Staffing the Right Players to Succeed Chapter 14: Managing Upwards: Socialize If You Must, Prove Results Every Time Chapter 15: Best Friend Brands: Becoming Indispensable to Your Customer Chapter 16: Riding the Wave: Career Success Powered by Behavioral Marketing Chapter 17: Closing Thoughts and The Power of Actions Index.
Includes bibliographical references.
Print version record and CIP data provided by publisher.
Keywords: Internet marketing; Customer relations; Consumers' preferences; BUSINESS & ECONOMICS -- Marketing -- General; Consumers' preferences; Customer relations; Internet marketing; Electronic books; Electronic books